Host response in periodontology: The defensive shield of the supporting structures of teeth - Dhirendra Kumar Singh; Jugajyoti Pathi (Wolters Kluwer Medknow Publications, 2021)
Oral microbial infections produce a significant rise in systemic inflammatory responses, manifested by acute-phase cytokines and acute-phase inflammatory reactants. Therapeutic oral manipulations or the inappropriate or absence of intervention of progression periodontal disease could have a significant influence on these systemic diseases. Periodontal pathologies usually refer to common inflammatory disorders known as gingivitis and periodontitis, which are caused by pathogenic microorganisms present in the subgingival dental plaque, and cause an inflammatory response. These Inflammatory response process results in the destruction of periodontium, and eventually in tissue, which further leads to tooth loss. The present article explains the role and significance of the host response in periodontal diseases.